Antioxidant Activity of Pineapple Peel (Ananas comosus L.) Ethanol Extract Using CUPRAC and FRAP Methods - Sitepu, Debi Dinha Octora; Maharani, Maharani (CV. Nusantara Scientific Medical, 2025)
Pineapple peel (Ananas comosus L.) is an agricultural by-product rich in phenolic compounds and flavonoids that may possess significant antioxidant properties. This study aimed to evaluate the antioxidant activity of 70% ethanol extract of pineapple peel using two complementary spectrophotometric methods: CUPRAC (Cupric Reducing Antioxidant Capacity) and FRAP (Ferric Reducing Antioxidant Power). The extraction was performed by maceration method yielding 14.77 ± 0.52% extract. Phytochemical screening confirmed the presence of flavonoids, tannins, phenolics, saponins, and terpenoids. Total phenolic content (TPC) was 68.42 ± 2.31 mg GAE/g and total flavonoid content (TFC) was 42.67 ± 1.84 mg QE/g. The CUPRAC method at 450 nm yielded a TEAC value of 312.5 ± 8.2 μmol TE/g, while the FRAP method at 593 nm yielded 198.4 ± 5.6 μmol Fe²⁺/g. EC50 values were 186.4 ± 6.3 μg/mL (CUPRAC) and 228.3 ± 7.4 μg/mL (FRAP), which were lower than vitamin C as positive control (89.7 ± 3.8 and 112.5 ± 4.2 μg/mL, respectively). Pearson correlation showed strong positive correlations between TPC/TFC and antioxidant activity (r = 0.9873 and 0.9645, p < 0.01). These results indicate that pineapple peel ethanol extract possesses moderate antioxidant activity attributable primarily to its phenolic and flavonoid content, warranting further studies on bioactivity-guided fractionation.